Zircônia CO-dopada por compensação de cargas nos sistemas (ZrO2)1-(x+y)(InO1,5)x(MOz)y com MOz = TaO2,5, NbO2,5, MoO3 ou WO3, como revestimento para barreira térmica - Piva, Roger Honorato (2016)
InO1.5-stabilized zirconia (InSZ) is a potential hot corrosion resistant thermal barrier coating (TBC). However, the thermal instability prevents real applications of InSZ-based TBC. This thesis investigates the hypothesis of co-doping using the charge compensation to improve the phase stability of InSZ. Four co-doping systems were synthesized by coprecipitation and studied: (ZrO2)1-(x+y)(InO1.5)x(MOz)y with MOz = TaO2.5, NbO2.5, MoO3, or WO3. After synthesis, 9 mol% of InO1.5 plus the charge-compensating oxides was sufficient to stabilize the tetragonal phase. Specific surface area up to 106.1 m2.g-1 and crystallite size ~11 nm were achieved using ethanol washing followed by azeotropic distillation as dehydration technique in the precipitates. In these powders, initial thermal stability analysis indicated instability of the tetragonal phase, with extension of the t→m transformation less detrimental in the InMoSZ system. Further increase in the concentration of InO1.5:MoO3 results in monophasic samples with retention of cubic phase in the InMoSZ. Cubic InMoSZ exhibited hardness and thermal expansion coefficient of 13.5% and 9% higher than those of InSZ, respectively. However, thermal treatments at T ≥ 1200 °C showed that the InMoSZ is also passive to destabilization of the high temperature cubic polymorph. Although the cubic InMoSZ was the most promising system found in this thesis, the stability results do not support its application as TBC for temperatures ≥ 1000 ºC. A deep evaluation of the phase transformations between 1000 to 1200 °C indicated that the instability of the proposed systems is due to a progressive c→t→m destabilization of the polymorphs. This c→t→m transformation is directly associated with the reduction of the InO1.5 stabilizer in solid solution by volatilization as In2O during heat treatment. At temperatures ≤ 800 ºC, the c→t phase transformation do not occurs, then, InSZ-based TBC is stable in these conditions.